تطور السياسة السكانية في سوريا (Latakia University Journal - Economic and Legal Sciences Series, 2019)
إن موضوع الثقافة السكانية ودراستها تعبر عن الاهتمام الكبير والعناية الفائقة بالإنسان وعن التفكير العلمي والاجتماعي بإنسانية الإنسان وكرامته، والسعي إلى توفير الحياة اللائقة به، وتحقيق رفاه له في صورتها الاجتماعية ضمن إطار المجتمع، وتحقيق رفاهية الأسرة التي هي عماد بنائه الاجتماعي. لذلك كله لابد من إعطاء العامل السكاني دوره الأساسي في صياغة خطط التنمية، لتلبي حاجات المواطنين وتساهم في بناء حياة كريمة لهم. سنحاول في هذا البحث إلقاء الضوء على واسع السياسة السكانية في سوريا، وعلى الخطط المستقبلية لها على المدى البعيد. وتعتبر التنمية السكانية أحد أهم محاور التنمية الشاملة وتهدف إلى تحقيق مؤشرات إيجابية في معدلات النمو السكاني والتعليمي والصحي والسكاني، وهي بالتالي تهدف إلى تحقيق واقع أفضل ورخاء أكثر للإنسان. The study of demographic education expresses a great interest in the human being and the social and scientific thinking of man and his dignity. Demographic education seeks to provide man with decent life to help him achieve social prosperity in society, and make the family, which is the essential part in the society, live in perfect conditions. Thus, the demographic factor must play its basic role of formulating development plans that fulfill the needs of citizens and contributes to giving them the best way of life. In this paper, we’ll shed light on the situation of the demographic policy in Syria, and on the prospective plans. The demographic development is considered one of the main trends of comprehensive development. It aims to achieve positive indicators of the rates of demographic, educational, and health development; so the goal is to achieve a better situation and more welfare for man.